TYPES OF CASUAL LANGUAGE USED IN TEENLITS NOVEL - Ronny Destoriandi, Rusdi Noor Rosa (p: 239-244) (English Language and Literature, 2013)
Teenlits is one of reading a novel is very well known and very popular with teenagers. Inside there teenlits types of non-standard language and Colloquial slang is often used by teens today in communicating. According to the teens communicate using slang words and Colloquial can facilitate a relationship and make a more compelling communication. But not all teenagers understand the slang words and the Colloquial, slang words and popular Colloquial used by a particular group or community.The purpose of this paper is to know about the non-standard form of the language contained in teenlits. The data is in the can by reading and researching novel and Colloquial slang word, mark and write it on paper, after which the data in the analysis by classifying and Colloquial slang. From these data there is a number of slang and Colloquial 60 words 38 words.From the above findings show that non-standard form of the language is a formal language that is not always used by teens in everyday life. Keywords: Teenlits, Colloquial, Slang, word.